Sustainable Economic Empowerment through Serbuk Sawo Drajat as a Natural Sugar Substitute: A Participatory Action Research Approach in Lamongan, Indonesia - Siti Shoimah; Nawari Nawari; Mahfud Sudarsono; Muhammad Tegar Bayu Pamukti; Muhammad Hanafi Fahmi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Desa Drajat in Lamongan Regency is a major producer of Sapodilla (Manilkara zapota), locally known as Sawo. Its high perishability, however, consistently results in 20–30% post-harvest losses, posing substantial economic challenges for farmers and local Micro, Small, and Medium Enterprises (MSMEs). This study aims to empower the community through the KKN Tematik program by Universitas Islam Darul 'Ulum (UNISDA) Lamongan, employing a Participatory Action Research (PAR) approach. The program centers on converting fresh Sapodilla into Serbuk Sawo Drajat, a natural powdered sweetener derived from local fruit that aligns with Green Economy and Circular Entrepreneurship principles. The methodology covered four stages: planning, action (training on processing and packaging), observation, and reflection. Findings indicate a marked increase in partner capacity: zero-waste understanding rose by 85%, processing proficiency by 90%, and digital marketing awareness by 80%. This product successfully extends the shelf life of Sawo to 12 months and raises its economic value, thereby strengthening community-based sustainable economic resilience.